1861 Conn. Acts 95, An Act In Addition To And In Alteration Of “An Act Relating To The Militia,” chap. 73, § 8 - (:unkn) unknown (General Publisher, 1861)
Required the quarter-master general to provide a suitable armory for each company of active militia which has organized according to law.
--
Keywords: ARMED FORCES